2011
DOI: 10.2527/jas.2010-2861
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selection for decreased residual feed intake on composition and quality of fresh pork1

Abstract: The objectives of this study were to determine the extent to which selection for decreased residual feed intake (RFI) affects pork composition and quality. Pigs from the fifth generation of selection for decreased RFI (select) and a randomly selected line (control) were utilized. Two experiments were conducted. In Exp. 1, barrows (22.6 ± 3.9 kg) from select and control lines were paired based on age and BW. The test was conducted in 8 replicates of pairs for the test period of 6 wk. Calpastatin activity and my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
47
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 34 publications
9
47
5
1
Order By: Relevance
“…We have reported the unique protein profile and PTM differences in comparisons of pigs that were genetically and phenotypically divergent in feed efficiency during the growing period. The differences in growth performance reported in these comparisons are consistent with previously published results from these same lines of pigs (Cai et al, 2008;Grubbs et al, 2013b;Harris et al, 2012;Smith et al, 2011) and another similar swine RFI genetic selection project (Barea et al, 2010;Lefaucheur et al, 2011). Phenotypic differences in RFI without genetic selection for RFI have also been reported in cattle Table 5.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We have reported the unique protein profile and PTM differences in comparisons of pigs that were genetically and phenotypically divergent in feed efficiency during the growing period. The differences in growth performance reported in these comparisons are consistent with previously published results from these same lines of pigs (Cai et al, 2008;Grubbs et al, 2013b;Harris et al, 2012;Smith et al, 2011) and another similar swine RFI genetic selection project (Barea et al, 2010;Lefaucheur et al, 2011). Phenotypic differences in RFI without genetic selection for RFI have also been reported in cattle Table 5.…”
Section: Discussionsupporting
confidence: 82%
“…Before the fifth generation, the high RFI line was a randomly selected control group, meaning genetic selection for high RFI lags 5 generations behind the selection for low RFI in the low RFI line. As with previously published reports in genetic selection for RFI in pigs, there was no difference in the final BW between the lines (Lefaucheur et al, 2011;Smith et al, 2011). Data from this study and previously published reports Harris et al, 2012) on these same lines of pigs indicate that genetic selection for RFI may provide a good model for understanding molecular differences in RFI when compared to single phenotypic comparisons.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Across muscles, μ-and m-calpain activities tended to be lesser (P = 0.10 and 0.09, respectively) in muscle from the more efficient low RFI pigs compared with high RFI pigs (Table 2). Furthermore, total calpastatin activity was greater (P < 0.05) in muscle from low RFI pigs, which is consistent with previous findings in younger pigs (Smith et al, 2011). The difference in total calpastatin activity can be attributed primarily to differences in calpastatin II activity (P = 0.01), given that activity of calpastatin I was not different between lines (P = 0.79).…”
Section: Methodssupporting
confidence: 81%
“…In the Iowa State University RFI Yorkshire pig selection project, pigs in the low RFI line are more efficient and tend to have less carcass fat, greater carcass lean, and lesser ADG compared with control and high RFI lines (Cai et al, 2008;Smith et al, 2011;. Boddicker et al (2011a,b) reported a trend for increased protein and decreased fat composition in carcasses from Yorkshire pigs selected for low RFI compared with the control line.…”
Section: Introductionmentioning
confidence: 99%